Reconnaissance for Radioactive Deposits in Selected Areas of the Lower Yukon-Kushkokwim Region, Alaska, 1952 - West, Walter S. (Geological Survey (U.S.), 1953)
Report discussing the investigation of zeunerite-related radioactivity and molybdenite-related radioactivity occurrences in the lower Yukon-Kuskokwim region, Alaska. Discussion of the data, methods and purpose of investigation, and location of radiation are included.